Carlos Rojas González (Guayaquil, 1941-2019): teorizar y pensar desde la escritura poética (In Memorian) - Báez Meza, Marcelo (2022)
A journey through the textual production of one of the most solid voices in Ecuadorian poetry. A look at each of the books that Carlos Rojas González, from Guayaquil, has published since 1990. One of the few writers who combined the sciences of language with poetic praxis. His work can be summarised as the semiotics of a double passion: that of women and the beloved city. The neatness of his phrasing and conceptual richness are two of the many contributions of a semiotician who put maximum tension into poetic discourse.